2004
DOI: 10.3141/1883-18
|View full text |Cite
|
Sign up to set email alerts
|

Normal Acceleration Behavior of Passenger Vehicles Starting from Rest at All-Way Stop-Controlled Intersections

Abstract: Acceleration characteristics of passenger cars starting from rest are often used in traffic simulation, modeling of vehicle fuel consumption and emissions, and design of intersections, acceleration lanes for entrance terminals, turning bays, and passing lanes. Most of the previous studies developed four different acceleration models: the constant acceleration model, the two-phase model, the linear-decreasing acceleration model, and the polynomial acceleration model. However, most of the studies were based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 2 publications
10
49
1
5
Order By: Relevance
“…The dynamic speed profiles of three participants are illustrated in Figure 3. The results confirm the findings of Wang et al (2004), that the constant acceleration assumption does not reflect realistic, actual driver behaviour. After analysing 40 different driver simulator runs, it was found that the process consists of only two main operational states, namely, transition (state 1) and acceleration (state 2).…”
Section: B31 Data Collection and Vehicle Operation Classificationsupporting
confidence: 86%
See 1 more Smart Citation
“…The dynamic speed profiles of three participants are illustrated in Figure 3. The results confirm the findings of Wang et al (2004), that the constant acceleration assumption does not reflect realistic, actual driver behaviour. After analysing 40 different driver simulator runs, it was found that the process consists of only two main operational states, namely, transition (state 1) and acceleration (state 2).…”
Section: B31 Data Collection and Vehicle Operation Classificationsupporting
confidence: 86%
“…Generally, an assumption of constant acceleration is implemented by most micro-simulation packages. However, Wang et al (2004) have assumed that drivers normally accelerate with a polynomial decreasing relationship with speed. Long (2000) has concluded that linearly decreasing acceleration rates better represent both maximum vehicle acceleration capabilities and actual motorist behaviour.…”
Section: A6mentioning
confidence: 99%
“…The published results of Hirschmann [4], Rakha [6] and Wang [7] suggest that the most probable acceleration values for stop line accelerations are in the 1 to 2 mls 2 range with peak accelerations are in the 3 to 4 mls 2 range. Our results support that findings with a slightly higher peak acceleration observed.…”
Section: A Speed and Accelerationmentioning
confidence: 93%
“…The study showed the desired acceleration rates from the VISSIM simulation model are too high by default, and suggested that these parameters need to be calibrated against the real world measurement before the model can be used to calculate for emissions. The acceleration values determined from this study are from 0 to 4 mls 2 • Other research into the vehicle acceleration at signalized junctions ( [5], [6], [7]) has focused on developing different models for estimating vehicle acceleration levels; in [6],the study proposed a vehicle dynamic model for predicting maximum acceleration for passenger vehicle. The model predicted values of acceleration range between 0 -4.3 mls 2 for the tested vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…This generic profile is set with a 2.4 m/s² deceleration rate, which is the average rate at 50 km/h according to [20]. This is a typical generic profile that may be used for ADAS applications.…”
Section: A Gaussian Processes Based Modellingmentioning
confidence: 99%